Changes in biological factors of fertility in managed Eucalyptus plantations on a savanna soil in Congo - Bernhard-Reversat, F.; Laclau, J.P.; Loubana, P.M.; Loumeto, Jean Joël; Mboukou, I.M.C.; Reversat, G. (Center for International Forestry Research, 2001)
Biological factors of fertility were assessed through the study of litter quantity and quality, soil organic matter quantity and quality, soil microfauna, soil macrofauna, organic matter dynamic, particularly decomposition and non-symbiotic nitrogen fixation in an age series of Eucalyptus PF1 and one stand of E. urograndis (E. urophylla x E. grandis). The litter system underwent drastic changes with plot age: litter fall was higher in the older plots than in the younger ones. Soluble carbon and lignin content decreased significantly with plot age and decomposition rate increased. Change in soil organic matter amount occurred in the top layer of soil only and increased with plot age. This enhanced cation exchange capacity. Increase in soil organic matter content was due to the light organic fraction (>0.05 mm), and the amount of C did not change in the organo-mineral fraction. Soil organic matter quality changed also, and the C/N ratio increased with plot age. A drastic decrease in free living nematode density from savanna to young plantations was observed after which it increased slowly with plot age although in the 19-year-plots it was still about ten times lower than in savanna. The importance of Xiphinema parasetariae, a parasite of eucalypts, was confirmed. Its density increased markedly with plot age and the size of the patches where it occurred increased. All soil macrofauna, earthworms, termites and litter inhabiting groups, except the ant group, increased in density with plot age. Termite density decreased in logged stands but no other measured parameters showed any significant difference between plantations and clear felled areas. The long-term effect of harvesting was observed mainly in the litter system and it appeared to be strongly disturbed by previous logging. Previous logging did not affect soil organic matter and nematode populations, either free living or plant parasitic. Soil macrofauna groups slightly increased after harvesting. Total phenolic compounds and fibre content were very different in leaf litter among clones and hybrids.